Analisis Historis Perumusan Pembukaan UUD 1945 - Rohman, Fatkhur; Adawiyah, Robiatul; Zahra, Rokhima Fatimah; Eka, Syayyidah Alifah; Sa'adah, Nila Lafifatus; Anbiya, Bakti Fatwa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The preamble to the 1945 Constitution reflects the great enthusiasm of the Indonesian people in fighting to achieve independence and build a sovereign state. Historical analysis of the formulation of the preamble to the 1945 Constitution is important to understand the historical flow and values contained in the process of formulating the preamble to the 1945 Constitution and the figures who played an important role in it. The purpose of this research is to remind readers that the opening of the 1945 Constitution was not born out of thin air, but was motivated by worrying social and political conditions in the past, where the Indonesian people were still colonized and not yet independent. This research uses a historical analysis approach to reveal the historical flow of the formulation of the preamble to the 1945 Constitution until its completion. Data was obtained from primary sources, namely the BPUPKI Session Minutes book, as well as relevant secondary sources. The process of formulating the preamble to the 1945 Constitution began on April 29 1945 with the formation of BPUPKI and ended with the reading and ratification on August 18 1945 by the Indonesian Independence Preparatory Committee (PPKI). The results of this research provide in-depth insight into the historical flow of the formulation of the preamble to the 1945 Constitution as well as the values contained in it and the figures who played an important role in it. This article provides implications in strengthening understanding of the history of Indonesia's struggle for independence and the values contained in the Preamble to the 1945 Constitution. However, it has limitations in its limited focus on historical analysis, lack of inclusion of contemporary perspectives, and limited historical sources available for research.